Pitch and depth control of underwater glider using LQG and LQR via Kalman filter - Ullah, B. (MechAero Found. for Techn. Res. and Educ. Excellence, 2018)
Underwater gliders are adversely affected by ocean currents because of their low speed, which is compounded by an inability to make quick corrective manoeuvres due to limited control surface and weak buoyancy driven propulsion system. In this paper, Linear Quadratic Regulator (LQR) and Linear Quadratic Gaussian (LQG) robust controllers are presented for pitch and depth control of an underwater glider. The LQR and LQG robust control schemes are implemented using MATLAB/Simulink. A Kalman filter was designed to estimate the pitch of the glider. Based on the simulation results, both controllers are compared to show the robustness in the presence of noise. The LQG controller results shows good control effort in presence of external noise and the stability of the controller performance is guaranteed. Â© 2018.